ROS robotics projects : build a variety of awesome robots that can see, sense, move, and do a lot more using the powerful Robot Operating System /: build a variety of awesome robots that can see, sense, move, and do a lot more using the powerful Robot Operating System. (2017) - Joseph, Lentin
No abstract available